Management of hemodynamically unstable patients with fracture pelvis Mafraq Hospital experience, UAE - Alkatary, Mohammed; Miller, Jody Robert; Al Ayoubi, Fawzi (International Surgery Journal, 2017)
Background: Multidisciplinary team and multiple approaches were introduced to improve the outcome after significant pelvic trauma. In present study, we are evaluating our institutional management modalities for unstable patients with unstable pelvic fractures using angio-embolization, pelvic packing with or without angio-embolization and conservative management with surgical intensive care unit (SICU) admission. Methods: We reviewed 108 patients admitted with pelvic fractures from January 2013 to September 2014, 19 patients (17.5%) were hemodynamically unstable with pelvic fracture. Massive transfusion protocol was activated in all patients. FAST scan was done. Level 1 trauma CT for the responder and transient responder patients. Results: Out of 19 patients, 7 patients (36.8%) were good responders to resuscitation with maintaining of their hemoglobin stable, with no extravasation of dye, admitted to SICU for conservative management. 4 patients (21%) were responders with CT trauma revealed dye leak so they underwent angio-embolization, SICU admission. 8 patients (42.1%) were non-responders underwent preperitoneal packing, one of them had additional angio-embolization. Conclusions: Preperitoneal packing is an excellent choice for non-responder patients, while angio-embolization can be done for responder and transient responder patients with evident dye extravasation. This study needs more evaluation on a wider clinical scale.